2019
DOI: 10.4000/eces.4350
|View full text |Cite
|
Sign up to set email alerts
|

Contexto económico y determinantes sociales de la accidentabilidad laboral en el sur de Europa. Los casos portugués y español

Abstract: El modelo neoliberal de gestión de la crisis económica (austeridad, precariedad laboral y recortes en el Estado de Bienestar) ha provocado un aumento de las desigualdades sociales, la desregulación del mercado de trabajo y el debilitamiento de sus principales instituciones (derecho del trabajo, sindicatos y negociación colectiva), operando, asimismo, como factores determinantes del repunte en los índices de accidentes laborales, especialmente en el sur de Europa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…With regard to socioeconomic conditions, it is important to maintain a constant information flow and to maintain data updated, since most of these conditions have a direct impact on accident rate. This fact is evidenced in a study on accidentability in southern Europe conducted by Castiblanque, 9 whose analysis of accident rates by sex revealed that men were more likely to suffer an accident than women and that, if considering psychosocial conditions, such as occupational diseases, the rates of accidents could increase to 40% compared to women. With regard to age, the author reports that young individuals tend to exhibit greater accident rates than adult individuals; as for employment relationship, people with temporary employments were found to have a higher rate of occupational accidents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With regard to socioeconomic conditions, it is important to maintain a constant information flow and to maintain data updated, since most of these conditions have a direct impact on accident rate. This fact is evidenced in a study on accidentability in southern Europe conducted by Castiblanque, 9 whose analysis of accident rates by sex revealed that men were more likely to suffer an accident than women and that, if considering psychosocial conditions, such as occupational diseases, the rates of accidents could increase to 40% compared to women. With regard to age, the author reports that young individuals tend to exhibit greater accident rates than adult individuals; as for employment relationship, people with temporary employments were found to have a higher rate of occupational accidents.…”
Section: Discussionmentioning
confidence: 99%
“…Lima (2002), cited in Castiblanque, 9 states that occupational safety and health problems observed in a study conducted in Spain and Portugal are associated not only with technical characteristics, but it is also important to consider employees’ social elements and cultural habits. Moreover, it is necessary to establish and identify these aspects, since they have a direct impact on accident rates, according to individual conditions, such as age, stress, depression, economic factors, and other conditions that create a block of information that enables to understand that conditions of occupational safety and health are related to company’s internal and external factors.…”
Section: Introductionmentioning
confidence: 99%